Non-stenosing Carotid Atherosclerosis and Arterial Stiffness in Embolic Stroke of Undetermined Source - Acampa, Maurizio; Lazzerini, Pietro Enea; Manfredi, Chiara; Guideri, Francesca; Tassi, Rossana; Domenichelli, Carlo; Cartocci, Alessandra; Martini, Giuseppe (Frontiers in Neurology, 2020)
Background and Purpose: Recent findings suggested that non-stenosing atherosclerosis (NSA) may play an important pathogenic role, especially in cryptogenic strokes. Furthermore, arterial stiffness has been suggested to be a useful tool in identifying patients with embolic stroke of undetermined source (ESUS) with poor neurological prognosis. In this view, the aim of our study was to assess the association between carotid NSA and arterial stiffness in ESUS patients, in order to better define the cardiovascular risk profile of this subgroup of patients. Methods: We enrolled 100 patients with ESUS (52 males, 48 females) and 48 patients with ischemic stroke from atherosclerosis. All patients underwent clinical and neuroimaging examination. A 24-h heart rate and blood pressure monitoring was performed in order to evaluate systolic, diastolic and mean blood pressure, pulse pressure, and arterial stiffness index (ASI). Results: NSA was present in 48 patients. In comparison with non-NSA-ESUS, in NSA-ESUS the mean age was higher, neurological deficit was more severe, hypertension, and diabetes were more common; systolic blood pressure, pulse pressure, and ASI were higher. In particular NSA-ESUS had ASI levels similar to strokes due to atherosclerosis. Conclusions: Our findings shed light on specific cardiovascular risk profiles underlying different subtypes of ESUS, suggesting the presence of increased arterial stiffness in NSA-ESUS patients with a risk factors profile similar to strokes due to atherosclerosis.